Peranan KSP Kopdit Pintu Air dalam Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) di Cabang Maumere - Viktorius Densius Moa Mori; Henrikus Herdi; Paulus Libu Lamawitak (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
The research aimed to analyze the role of KSP Kopdit Pintu Air in the development of Micro, Small, and Medium Enterprises in the Maumere Branch. The research method employed a qualitative descriptive analysis approach. The data collection methods included observation, interviewes, and documentation. The data sources used in this research were both primary and secondary data. The research involved 7 informants, including 3 employees of KSP Kopdit Pintu Air and 4 micro, small, and medium enterprise (UMKM) actors. The research’s results indicated that KSP Kopdit Pintu Air played a role in providing capital for micro, small, and medium enterprises. The also act as marketing facilitators, aiding members in promoting their business results. However, it’s important to note that KSP Kopdit Pintu Air did not offer entrepreneurship training, seminars, or workshops for their members. Additionally, the mentoring provided to member businesses was limited to monthly meetings for motivation, and the financial facilitators had not received training in financial management.